Eksistensi Tokoh Perempuan dalam Novel Mustika Zakar Celeng Karya Adia Puja: Analisis Feminisme Eksistensial - Ramadhan, Maharani Syifa; Zurmailis, Zurmailis; Sukmawati, Noni (TSAQOFAH, 2024)
The novel Mustika Zakar Celeng by Adia Puja was chosen as the object of research. This study focuses on how the marginalization of women as Others in a patriarchal environment and how they resist as a form of existence, as depicted by the characters Nurlela, Lilis Komariah, and Kelanti. The three female protagonists are assertive female characters who struggle to be accepted as equal beings with men who especially have the freedom to reject things that are not in line with their existence. In this study, researchers chose a feminist approach. Because this research has a female perspective, the genre chosen for this research approach is feminism. Simone de Beauvoir's theory became the theoretical basis for this research analysis. According to Simone de Beauvoir, women are just the Other for men in life. Men are subjects and women are objects. According to Beauvoir, existentialism is a state when women are no longer objects but subjects in themselves. Descriptive research methodology with a qualitative approach is used in this research. Critical phenomenology, especially existentialist feminist phenomenology, is the research methodology used in this study to reveal and show the existence of women and the relationship between the subject and object of study. There are three forms of marginalization of female characters as Others in this study, including: 1) stereotyping of women, 2) subordination of women, 3) violence against women. From these forms of marginalization, there are three forms of resistance of female characters as a form of existence, including: 1) working 2) doing intellectual activities in daily life 3) rejecting the internalization of her womanhood through words and actions.